WORD FORMATION PROCESSES OF THE JARGON USED BY BARISTA IN COFFEE CORNER MALANG - KANA, ANANDINA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study was conducted to find out the jargon used by barista in CoffeeCorner Malangand also its word formation processes. The writer tookbarista in Coffee Corner Malang as the data source since they are classifiedas qualified baristas.  Furthermore, the writer took six steps in analyzingthe data: underlining the utterances, coding the data, classifying the data,analyzing the data found, discussing the finding and drawing conclusion.The result show that there are 77 jargons used by barista in Coffee CornerMalang. The writer also found 6 process of 10 word formation processes inthe jargon used by barista in Coffee Corner Malang, there are borrowing,coinage, compounding, acronym, derivation, and multiple processes. Fromthe findings, we can conclude that barista jargons is a languagephenomenon that really exists and becomes a part of  language variationand word formation process also take important roles in languagedevelopment. Keywords: word formation process, jargon, barista, Coffee Corner Malang